Analisis Kegagalan Struktur Ruang Aula Gedung Serbaguna Kabupaten Pidie Jaya - Cut Nella Asyifa; Muttaqin Muttaqin; Mochammad Afifuddin (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2019)
Aceh is one of the provinces in Indonesia at risk of earthquakes. On December 7, 2016, a magnitude 6.8 earthquake occurred in which is Pidie Jaya District at coordinates of 5.25 LU and 96.24 east longitude. One of the buildings having failure construction because of the earthquake is Hall Room of Multipurpose Building of Pidie Jaya District. Column in the front of the hall has a large permanent deformation, so it can be said that the structure has failed. The purpose of this research is to know the cause of the structural failure with the help of software SAP2000 version19 and compared it to SNI 1727-2013 and SNI 1726-2012. Hall Room of Pidie Jaya District which has 10 m height is modeled as space frame then analyzed with dynamic response spectrum. Two models of analysis were created; is that model 1 with structure as existing condition and model 2 with structure modification. The results obtained the largest capacity ratio of beam is 2.216 and column is 1.198, the largest lateral displacement at the direction of Y on the first floor is 321,334 mm, the second floor is 631,997 mm and the third floor is 782,954 mm. The largest story drift in the direction of Y on the first floor was 321,334 mm, on the second floor was 310,663 mm and the third floor was 150,958 mm. The cause of failure structure of Hall Room Multipurpose Pidie Jaya District is the small stiffness of the structure in the direction of Y.